The Cambridge companion to Freud - Neu, Jerome (Cambridge, United Kingdom Cambridge University Press, 1991)
Does Freud still have something to teach us? The premise of this volume is that he most certainly does. Approaching Freud from not only the philosophical but also historical, psychoanalytical, anthropological, and sociological perspectives, the contributors show us how Freud gave us a new and powerful way to think about human thought and action. They consider the context of Freud's thought and the structure of his arguments to reveal how he made sense of ranges of experience generally neglected or misunderstood. All the central topics of Freud's work from sexuality and neurosis to morality, art, and culture are covered. -- Back cover.
Freud : the psychoarcheology of civilizations / Carl E. Schorske -- Seduced and abandoned : the rise and fall of Freud's seduction / Gerald N. Izenberg -- Freud's androids / Clark Glymour -- The interpretation of dreams / James Hopkins -- The unconscious / Sebastian Gardner -- The development and vicissitudes of Freud's ideas on the Oedipus complex / Bennett Simon and Rachel B. Blass -- Freud and perversion / Jerome Neu --Morality and the internalized other / Jennifer Church -- Freud on women / Nancy J. Chodorow -- Freud and the understanding of art / Richard Wollheim -- Freud's anthropology : a reading of the "cultural books" / Robert A. Paul -- Freud's later theory of civilization : changes and implications / John Deigh.
Includes bibliographical references (pages 339-342) and index.
Keywords: Freud, Sigmund -- 1856-1939.; Psychoanalysis; Freudian Theory -- Biography; Psychoanalysis -- Biography